An International Consensus Definition of the Wish to Hasten Death and Its Related Factors. - Albert Balaguer; Cristina Monforte-Royo; Josep Porta-Sales; Alberto Alonso-Babarro; Rogelio Altisent; Amor Aradilla-Herrero; Mercedes Bellido-Pérez; William Breitbart; Carlos Centeno; Miguel Angel Cuervo; Luc Deliens; Gerrit Frerich; et al. (PLoS ONE, 2016)
BACKGROUND:The desire for hastened death or wish to hasten death (WTHD) that is experienced by some patients with advanced illness is a complex phenomenon for which no widely accepted definition exists. This lack of a common conceptualization hinders understanding and cooperation between clinicians and researchers. The aim of this study was to develop an internationally agreed definition of the WTHD. METHODS:Following an exhaustive literature review, a modified nominal group process and an international, modified Delphi process were carried out. The nominal group served to produce a preliminary definition that was then subjected to a Delphi process in which 24 experts from 19 institutions from Europe, Canada and the USA participated. Delphi responses and comments were analysed using a pre-established strategy. FINDINGS:All 24 experts completed the three rounds of the Delphi process, and all the proposed statements achieved at least 79% agreement. Key concepts in the final definition include the WTHD as a reaction to suffering, the fact that such a wish is not always expressed spontaneously, and the need to distinguish the WTHD from the acceptance of impending death or from a wish to die naturally, although preferably soon. The proposed definition also makes reference to possible factors related to the WTHD. CONCLUSIONS:This international consensus definition of the WTHD should make it easier for clinicians and researchers to share their knowledge. This would foster an improved understanding of the phenomenon and help in developing strategies for early therapeutic intervention.